Evaluating emission trading as a policy tool : evidence from conditional jump models - Marc Gronwald; Janina Ketterer (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper, first, empirically investigates European emission allowance (EUA) prices and, second, evaluates emission trading as a policy measure. Applying combined jump GARCH models yields strong evidence of conditional jump behavior. This implies that EUA prices are subject to unexpected movements and that a considerable degree of uncertainty is present. According to the real option literature, uncertainty has adverse effects on investment decisions. Thus, investments in abatement technologies are likely to be postponed due to the peculiar characteristics of emission allowance prices. Furthermore, this price behavior is at odds with the theoretical notion that emission prices equal marginal abatement costs.
Keywords: C22; Q50; 330; emission allowance prices; jumps; GARCH; real options; Emissionsrechte; Preis; Emissionshandel; Volatilität; Umweltschutzkosten; Realoption; EU-Staaten